Agree to disagree: towards a peaceful co-existence amongst multi-religious community = Setuju untuk tidak bersetuju: kearah kehidupan aman bersama dikalangan masyarakat berbilang agama - U Tun Aung, Maulana Akbar Shah; Ali, Mohammed Farid; Afridi, Muhammad Adil Khan (IIUM Press, International Islamic University Malaysia, 2017)
Since the number of intricate problems with regard to peace and security faced by mankind on our sphere has been greater than what they can bear, the survival of human race on earth becomes a significant priority to be contemplated. Despite hard work and continued effort rendered by many experts, they face more serious issues and their resolutions are far from reality. It is because, in the author’s mind, rights and responsibilities are not properly observed. Particularly, in the area of religion people have lack of respecting the right of others and most of the times they are irresponsible. Every individual has their own choices according to their culture and belief which may not be acceptable to others. If every individual allows others to enjoy at their own choice while observing his own belief and tradition, we all can live in this world peacefully. This concept of living together with individual choice while respecting other’s choice may be called the concept of “agree to disagree” according to the author’s work. This ideology, which is yet to be well observed in our society, can surely replace violence with peaceful co-existence in the multi-religious and multi-cultural societies. Sejak masalah berkaitan dengan keharmonian dan keselamatan yang dialami manusia melebihi yang boleh ditanggung, kehidupan manusia di dunia ini menjadi satu keutamaan yang perlu dipertimbangkan. Walaupun banyak usaha dan langkah diambil oleh pihak pakar, mereka mengalami masalah lain yang lebih serius dan resolusi mereka adalah jauh dari matlamat. Ini kerana, dalam minda pengarang, hak dan tanggungjawab tidak diperhatikan dengan betul. Terutamanya dalam hal agama, orang kekurangan kehormatan terhadap hak orang lain dan kebanyakkannya adalah tidak bertanggungjawab. Setiap individu mempunyai kepercayaan dan hak masing-masing yang tidak boleh diterima oleh yang lain. Jika setiap individu membenarkan yang lain untuk mempunyai kepercayaan dan hak masing-masing, manusia semua boleh hidup dengan aman. Konsep ini boleh dipanggil sebagai konsep “setuju untuk tidak bersetuju” menurut kajian pengarang. Ideologi ini, yang masih belum diperhatikan dengan sepenuhnya dalam masyarakat kita, pasti boleh menggantikan keganasan dengan kehidupan aman bersama dalam masyarakat berbilang kaum dan budaya.